2018
DOI: 10.2320/matertrans.m-m2018809
|View full text |Cite
|
Sign up to set email alerts
|

Scorodite Synthesis in As(V)-Containing Fe(II) Solution in the Presence of Hematite as a Fe(III) Source

Abstract: Stabilization of arsenic by precipitation of large crystalline scorodite (FeAsO 4 •2H 2 O) particles is considered to be a promising option for treating As(V) contained in industrial by-products. In this study, scorodite synthesis by direct addition of hematite particles as a Fe(III) source to Fe(II) solution containing As(V) was investigated with different initial Fe(II) concentrations. During scorodite formation, the Fe(II) concentration and pH of the reaction solution are almost constant, and the residual a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 7 publications
2
15
0
Order By: Relevance
“…5) It was also suggested that hematite-seeds paly a role as the Fe 3+ source for scorodite formation. 10) In our biogenic studies, the positive effect of scoroditeseeds was also noted. 11,17) Since biomineralization reactions involve the interactions between the mineral, microbial cells (physicochemical as well as enzymatic effects) and reactant ions, the function of seed minerals within the biomineralization process can be complex.…”
Section: ¹supporting
confidence: 58%
See 2 more Smart Citations
“…5) It was also suggested that hematite-seeds paly a role as the Fe 3+ source for scorodite formation. 10) In our biogenic studies, the positive effect of scoroditeseeds was also noted. 11,17) Since biomineralization reactions involve the interactions between the mineral, microbial cells (physicochemical as well as enzymatic effects) and reactant ions, the function of seed minerals within the biomineralization process can be complex.…”
Section: ¹supporting
confidence: 58%
“…Therefore, the two-stage Asremoval was indeed found to play an important role in effective biogenic scorodite crystallization. 18) In abiotic scorodite crystallization studies by other researchers, the effect of seed-feeding (homogeneous scorodite or other heterogeneous minerals) was shown to be one of the influential factors: 3,5,10,19) Feeding scoroditeseeds allowed lowering the reaction temperature for scorodite crystallization (from 95 to 80°C). 3) Use of heterogeneousseeds such as hematite and gypsum were shown to be equally effective as homogeneous scorodite-seeds, where the authors suggested that hematite can outperform scorodite due to its "fine" properties.…”
Section: ¹mentioning
confidence: 99%
See 1 more Smart Citation
“…The reaction also occurs through gel-like precursor generation and its conversion to scorodite. In a previous study, 34) it was reported that the precursor contains Fe(II) as well as Fe(III). Furthermore, when Fe(II) is not contained in the solution, the formation reaction does not proceed even if hematite is added.…”
Section: Introductionmentioning
confidence: 97%
“…Scorodite synthesis by direct addition of solid Fe(III) compounds, namely hematite (Fe 2 O 3 ) 24,26,27) and magnetite (Fe 3 O 4 ), 28,29) to an FeSO 4 solution containing As(V) has also been reported. For hematite addition, the overall scorodite formation reaction can be expressed as shown in eq.…”
Section: Introductionmentioning
confidence: 99%